Sociocultural adaptation, educational ecosystem and quality of life among the international students community in Malaysia - En, Cui; Rosnon, Mohd Roslan; Abd. Razak, Muhammad Afiq; Amin, Samir Muhazzab (Human Resources Management Academic Research Society (HRMARS), 2023)
The difference in culture and education system makes the international student community adapt to the social changes, thus affecting their quality of life. Therefore, this study intends to examine the level of sociocultural adaptation and the Education ecosystem on the quality of life of the international student community in Malaysia. This study used quantitative methods with an exploratory research approach. 428 respondents were randomly chosen from five research universities: Universiti Putra Malaysia, Universiti Malaya, Universiti Teknologi Malaysia, Universiti Sains Malaysia and Universiti Kebangsaan Malaysia. Data were analysed descriptively and inferentially based on the objectives of the study. Overall, the study's findings show that the level of sociocultural adaptation is low, which is 55.1%, the educational ecosystem is high which is 57.2% and the quality of life is high, 52.1% among the international student community. In conclusion, the findings of this study show that international students in Malaysia experienced a good educational ecosystem and quality of life but have challenges adapting to socio-cultural. Therefore, higher education institutions in Malaysia need to pay attention to balanced development among the international student community to ensure that they can achieve well-being as outlined in the Fourth and Fifth Sustainable Development Goals.